2004
DOI: 10.1088/0953-8984/16/23/l02
|View full text |Cite
|
Sign up to set email alerts
|

The de Haas–van Alphen effect and the Fermi surface in CePt3Si and LaPt3Si

Abstract: We have carried out a de Hass-van Alphen (dHvA) experiment for the recently discovered CePt 3 Si, which is the first heavy fermion superconductor without inversion symmetry in the tetragonal crystal structure, together with a dHvA experiment for a non-4f reference compound LaPt 3 Si. As for LaPt 3 Si, several dHvA branches were observed. Among them, the two main dHvA branches with the dHvA frequency (the cyclotron effective mass) of 1.10 × 10 8 Oe (1.4 m 0 ) and 8.41 × 10 7 Oe (1.5 m 0 ) were found to be well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 15 publications
5
53
0
Order By: Relevance
“…23 As result of the various pressure studies, most notably it is found that the antiferromagnetic state is already suppressed at a pressure of about 0.6 GPa, while superconductivity persists up to a pressure of 1.5 GPa. Thus, for noncentrosymmetric CePt 3 Si the appearance of superconductivity is closely linked to the suppression of magnetic order, although here quantum critical behavior has not been observed in the various physical properties.…”
Section: 22mentioning
confidence: 99%
“…23 As result of the various pressure studies, most notably it is found that the antiferromagnetic state is already suppressed at a pressure of about 0.6 GPa, while superconductivity persists up to a pressure of 1.5 GPa. Thus, for noncentrosymmetric CePt 3 Si the appearance of superconductivity is closely linked to the suppression of magnetic order, although here quantum critical behavior has not been observed in the various physical properties.…”
Section: 22mentioning
confidence: 99%
“…Unfortunately, it is difficult to construct a reliable microscopic model for CePt 3 Si at the present moment, since experimental studies of microscopic electronic structure such as the de Haas-van Alphen effect have not yet succeeded in detecting the Fermi surface of heavy electrons in CePt 3 Si. 35 Very recently, Yanase and Sigrist have carried out microscopic calculations using the Fermi surface obtained by the LDA calculation, and found that the admixture of a p-wave state and an extended s-wave state is stabilized. 51 …”
Section: Pairing State Realized In Cept 3 Simentioning
confidence: 99%
“…[31][32][33][34] An intriguing feature of these systems is that according to LDA calculations and de Haas-van Alphen experiments, the SO splitting of the Fermi surfaces is much larger than the superconducting gap. 17,[35][36][37] For instance, in the case of CePt 3 Si, the magnitude of the SO splitting is nearly equal to 10 percent of the Fermi energy. 17,35 This large SO splitting indicates the important role of parity violation in these superconductors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, CePt 3 Si is the first heavy fermion superconductor with a lack of inversion symmetry of its crystallographic lattice 4 . This causes a spin-orbit splitting of the Fermi surface, which might generate chiral spin states 5 . A pure spin triplet pairing in such non-centrosymmetric system is excluded because of fundamental symmetry arguments 6 .…”
mentioning
confidence: 99%